Mentoring senior house officers. Is there a role for middle grade doctors?. Issue 4 (1st July 2001) - Okereke, C D; Naim, M
Abstract : Objectives —To determine whether the mentoring scheme currently used has an impact on the training of senior house officers and also determine if they are willing to accept middle grade mentors. Methods —A questionnaire comprising 10 questions was sent to all the senior house officers employed in the emergency departments of two large inner city teaching hospitals and three large district hospitals. Most of the questions required a simple yes/no response. Results —Most of the senior house officers had mentors allocated to them but felt the scheme was not satisfactory probably because they had low expectations. Most were happy to have middle grade doctors as mentors. Conclusions —Senior house officers have a low expectation of the present system and seem willing to accept middle grade doctors as mentors.